The Level of Production Specialization – Serbia and the New EU Member States - Mićić, Vladimir T; Savić, Ljubodrag P; Radičić, Dragana S (Industrija, 2018)
The paper examines the level and changes in production specialization (diversification) characteristic of the manufacturing industry of Serbia and the member states that joined the EU in 2004 and after. The authors aim to analyze the direction of structural changes in Serbia’s manufacturing industry and make comparison with the situation in the new EU member states, as well as determine whether those changes that show the same trends as GDP per capita movements are characterized by specialization growth, especially in terms of medium-high and high technology manufacturing activities. Industrial sector specialization index is used to determine the level of specialization of manufacturing industry production sectors and activities. Changes in specialization are analyzed by observing the changes in the mentioned index over a five-year period. The level of specialization of manufacturing sector is compared to the level of GDP per capita and its growth rate. In order to analyze the level of specialization of industry sectors and activities in Bulgaria, the Czech Republic, Estonia, Hungary, Lithuania, Romania, Slovakia, Slovenia and Serbia, the comparison method was used. The results of the research indicate that the direction of structural changes in Serbian manufacturing industry does not follow the usual pattern, i.e., the lower level of GDP per capita results in a higher level of production specialization, while the lower level of specialization and smaller number of activities leads to low technology intensity of production, which is not the case with the new EU member states.